Reducing acute kidney injury due to vancomycin in trauma patients. Issue 2 (August 2016) - Ko, Ara; Harada, Megan Y.; Barmparas, Galinos; Jay, Jessica; Sun, Beatrice J.; Chen, Eric; Mehrzadi, Devorah; Patel, Bansuri; Mason, Russell; Ley, Eric J.
Abstract : BACKGROUND: Supratherapeutic vancomycin trough levels are common after trauma and associated with both increased acute kidney injury (AKI) and mortality. We sought to limit the adverse effects of vancomycin in trauma patients through more frequent trough monitoring. METHODS: Beginning in January 2011, trauma patients treated with vancomycin had trough levels (VT) monitored daily until steady state was reached. Trauma patients admitted from January 2011 to May 2015 (POST) were compared with those admitted from January 2006 to December 2010 (PRE). Inclusion criteria required administration of intravenous vancomycin, admission serum creatinine (SCr), and SCr within 72 hours of highest VT. Acute kidney injury was defined as an increase in SCr of at least 0.3 mg/dL or 50% from admission to post–vancomycin administration. Those in the POST group were prospectively followed up until discharge or death. RESULTS: Two hundred sixty-three patients met inclusion criteria in the PRE-phase and 115 in the POST-phase. The two groups were similar in age, gender, race, body mass index, pre-existing comorbidities, admission systolic blood pressure, Glasgow Coma Scale, and head Abbreviated Injury Scale. Injury Severity Score was higher in the POST cohort (18 PRE vs. 25 POST, p < 0.001). Compared with PRE, the POST cohort had lower rates of supratherapeutic VT (>20 mg/L) (34.6% PRE vs. 22.6% POST, p = 0.02) and AKI (30.4% PRE vs. 19.1% POST, p = 0.026). After adjusting for confounders, the POST group had a significantly lower risk of AKI with an adjusted odds ratio of 0.457 ( p = 0.027). There was a trend toward decreased mortality in the POST cohort, but this did not reach significance (10% PRE vs. 5.2% POST, p = 0.162). CONCLUSIONS: A reduction in AKI was observed in trauma patients with daily vancomycin trough levels monitored until steady state. Increased awareness regarding closer surveillance of VT in trauma patients may limit the incidence of vancomycin-related nephrotoxicity. LEVEL OF EVIDENCE: Therapeutic study, level IV.